Connotations of the drive for domination and alienation in contemporary - poetic discourse - Amal Dunqul as an example - guenfoud, saadia (El Omda in Linguistics and Discourse Analysis, 2025)
. serve the nation and change its conditions for the better. "Amal Dunqul" is regarded as one of the most prominent poets who made their poetic discourse a mechanism for positive impetus, aiming to shape the present and future of the nation. Through his complete works, I was captivated by the powerful meanings with which he depicted the dominance and dispossession that the nation has been subjected to, affecting various aspects of its political, economic, social, and intellectual life. As echoed in his poems, the nation became like a dishonored woman, violated and stripped of her dignity. From this perspective, I sought to explore the meanings of dominance and dispossession, their relationship, and their manifestations in the poem "The Land .. The Unopened Wound," highlighting Amal Dunqul's skill in using history and applying it to the current reality of the nation